1993
DOI: 10.1177/070674379303800111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment and Alternative Care on Length of Stay on a General Hospital Psychiatric Unit — Results of an Audit

Abstract: Quality controls are becoming an important part of our health care system. A medical audit is one way of evaluating quality of care, and this paper describes the results of an audit conducted to investigate the reasons for a prolonged stay on a psychiatric inpatient unit. The results showed a decrease in the mean length of stay over a five year period, although the figure remained substantially above provincial norms. A review of the hospital charts of a random sample of one in six patients whose hospital stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…This is similar to previous studies [7,[14][15][16][17][18] which also observed that these disorders were associated with a longer hospital stay. Master et al explained that this group of disorders are chronic and debilitating, often requiring a longer time for resolution of symptoms and special forms of treatment such as drug dependence treatment and rehabilitation in therapeutic communities [14].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is similar to previous studies [7,[14][15][16][17][18] which also observed that these disorders were associated with a longer hospital stay. Master et al explained that this group of disorders are chronic and debilitating, often requiring a longer time for resolution of symptoms and special forms of treatment such as drug dependence treatment and rehabilitation in therapeutic communities [14].…”
Section: Discussionsupporting
confidence: 92%
“…This was in tandem with previous studies on LOS [14][15][16][17]. These variables are often associated with a worsening symptom severity [16,17].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…44 The shortage of beds in psychiatric hospitals and the resulting lack of vacancies for psychiatric hospitalization 45 cause PESs that support PHUGH to be overloaded by cases with comorbid clinical conditions, which demand longer hospitalization periods. 46 In larger metropolitan areas, following the increasing demand of emergencies in other clinical and surgical specialties, PESs end up functioning as hospital units as they maintain patients hospitalized for longer periods. 47 …”
Section: Psychiatric Emergency Services and General Hospitalsmentioning
confidence: 99%
“…Statistics on length of hospital stay are important in planning health care services (12). Most studies have found that patients diagnosed with comorbid psychiatric and medical disorders stay in hospital longer than inpatients with either a psychiatric or medical diagnosis (13).…”
Section: Administrative Issuesmentioning
confidence: 99%